C-Slate: Exploring Remote Collaboration on Horizontal Multi-touch Surfaces - Izadi, Shahram; Agarwal, Ankur; Criminisi, Antonio; Winn, John; Blake, Andrew; Fitzgibbon, Andrew (2007)
We introduce C-Slate, a new vision-based system, which utilizes stereo cameras above a commercially available tablet technology to support remote collaboration. The horizontally mounted tablet provides the user with high resolution stylus input, which is augmented by multi-touch interaction and recognition of untagged everyday physical objects using new stereo vision and machine learning techniques. This provides a novel and interesting interactive tabletop arrangement, capable of supporting a variety of fluid multi-touch interactions, including symmetric and asymmetric bimanual input, coupled with the potential for incorporating tangible objects into the user interface. When used in a remote context, these features are combined with the ability to see visual representations of remote users’ hands and remote physical objects placed on top of the surface. This combination of bimanual and tangible interaction and sharing of remote gestures and physical objects provides a new way to collaborate remotely, complementing existing channels such as audio and video conferencing.